Q. 105.0( 2 Votes )

Find , when

𝒳 = eθ (sin θ + cos θ), 𝒴 = eθ (sin θ - θ cos θ)

Answer :

Theorem: y and x are given in a different variable that is θ . We can find by finding and and then dividing them to get the required thing.


=


= eθ (cosθ + sinθ ) + (sinθ -cosθ )eθ ………..(1) {by using product rule, }



= eθ (cosθ - sinθ ) + eθ (sinθ + cosθ ) …………….(2) {by using product rule, }


Dividing (1) and (2), we get


=


=tanθ .


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses